Evaluation of Bacterial Contamination in Donated Blood for Transfusion Purposes at Kisii Teaching and Referral Hospital - Collince O. Ogolla; Rodgers N. Demba (Advances in Hematology, 2025)
Conclusion: S. epidermidis, S. aureus, Bacillus spp. and E. coli were among the isolated and identified bacteria found in donated blood samples among donors at KTRH.